Meteorological Observations at Schiaparelli Glacier Automatic Weather Station (AWSglacier), Cordillera Darwin, Chile, 2013-2019 - Jorge Arigony-Neto; Ricardo Jaña; Inti Gonzalez; Christoph Schneider; Franziska Temme (PANGAEA, 2023)
The publication series contains meteorological measurements from an automatic weather station installed on the glacier surface (140 m a.s.l. in September 2015) of Schiaparelli Glacier, Cordillera Darwin, Chile. The station has been installed by the Universidade Federal do Rio Grande, Brazil, in August 2013. The station fell into a crevasse in February 2015 and was reinstalled in September 2015. It measures 2m air temperature (T), relative humidity (RH), global radiation (G), air pressure (Pres), wind speed (U) and wind direction (Dir) in an hourly interval (hourly averaged). The data provided here has been corrected for outliers, radiative heating of the temperature sensor and sensor freezing. After the reinstallation in September 2015, an issue with the relative humidity measurements has been found. Relative humidity has been corrected using specific humidity from a nearby station (AWSrock) and air temperature, and included in the dataset as well (RHcorr).